2013
DOI: 10.1086/669524
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' Knowledge, Attitudes, and Practices regarding Infections with Multidrug-Resistant Gram-Negative Bacilli in Intensive Care Units

Abstract: Objective-To assess how healthcare professionals caring for patients in intensive care units (ICUs) understand and use antimicrobial susceptibility testing (AST) for multidrug-resistant gramnegative bacilli (MDR-GNB).Design-A knowledge, attitude and practice survey assessed ICU clinicians knowledge of antimicrobial resistance, confidence interpreting susceptibility testing, and beliefs regarding the impact of susceptibility testing on patient outcomes. Setting-16ICUs affiliated with New York-Presbyterian Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…We have demonstrated that XDR-GNB infections were associated with exposures to several antibiotics, some of which may be amenable to antibiotic stewardship [37]. Predictors for mortality after HAIs with XDR-GNB were not modifiable, as mortality was more likely to be associated with age and underlying diseases.…”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated that XDR-GNB infections were associated with exposures to several antibiotics, some of which may be amenable to antibiotic stewardship [37]. Predictors for mortality after HAIs with XDR-GNB were not modifiable, as mortality was more likely to be associated with age and underlying diseases.…”
Section: Resultsmentioning
confidence: 99%
“…The survey was also used to assess potential barriers to adherence to the guidelines by using the knowledge, attitudes, and practice paradigm developed by Cabana et al [11][12][13] Respondents' familiarity with the guidelines, agreement with specific recommendations, confidence in their ability to follow selected recommendations (self-efficacy), and perceptions of patients' benefits (outcome expectancy) were assessed. Both multiple choice format and Likert scales were employed in the survey.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…In case of high incidence of multidrug-resistant microorganisms and cumulative outbreaks, appropriate recommendations on diagnostic tests, evaluation of findings and treatment, as well as infection control management must be coordinated immediately and disseminated locally. There is generally great uncertainty about optimal treatment [ 394 ]. In certain circumstances, use of unconventional antimicrobials or of conventional antimicrobials in unusual dose and combination may become necessary.…”
Section: Recommendations Of the Guidelinementioning
confidence: 99%